Medial amygdala arginine vasopressin neurons regulate innate aversion to cat odors in male mice - Tong, Wen Han (2022)
Aversion to environmental cues of predators is an integral part of defensive behaviors in many prey animals. It enhances their survival and probability of future reproduction. At the same time, animals cannot be maximally defended because imperatives of defense usually trade-off with behaviors required for sexual reproduction like display of dominance and production of sexual pheromones. Here, we approach this trade-off through the lens of arginine vasopressin (AVP) neurons within the posterodorsal medial amygdala (MePD) of mice. This neuronal population is known to be involved in sexual behaviors like approach to sexually salient cues. We show that chemogenetic partial ablation of this neuronal population increases aversion to predator odors. Moreover, overexpression of AVP within this population is sufficient to reduce aversion to predator odors. The loss of fear of the predator odor occurs in parallel with increased recruitment of AVP neurons within the MePD. These observations suggest that AVP neurons in the medial aspect of the extended amygdala are a proximate locus for the reduction in innate fear during life stages dominated by reproductive efforts.